Pengaruh Umur Bulan Terhadap Hasil Tangkapan Sero - Reza Pebrian; Mariana E. Kayadoe; Lefrand Manoppo (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
Bambanipa Village is one of the villages in Palasa District, Parigi Moutong Regency, Central Sulawesi Province. Based on direct observations and interviews with local fishermen, the number of fishermen in the village of Bambanipa is 37 people. The research method used is descriptive and participatory. descriptive methods used are surveys and interviews. for data analysis using a randomized block design (RBD) model, with a mathematical formulation. During the research in the village of Bambanipa, the total number of catches was 318 individuals. With details based on the type of fish caught, namely Baronang (Siganus lineatus) 19 individuals, Grouper (Cromileptes altivelis) 1 individuals, Botana (Ctenochaetus striatus) 1 individual, Katamba (Lethrinus lentjan) 3 individuals, Dayah beard (Upeneus moluccensis) 3 individuals, Rengginan (Myripristis hexagonatus) 69 individuals, Tiger snapper (Plectorhinchus chaetodontoides) 2 individuals, Kuwe (Pseudocaranx dentex) 5 individuals, Black point snapper (Lutjanus fulviflamma) 3 individuals, Selar (Selar boops) 10 individuals, Sembilang (Euristhmus microceps) 200 individuals , 2 individuals of Cuttlefish (Sepia sp.).